Pengaruh Modal, Pembinaan, Dan Volume Usaha Terhadap Pemberdayaan Ekonomi Masyarakat Masjid Al-Musabbihin - Muhammad Yafiz; Roykhan Lbn Gaol (ITB AAS INDONESIA Surakarta, 2023)
The mosque is not only a place of worship but can also be used as a place for educational, economic, social activities and so on. This study aims to review the prospects for mosque-based community economic empowerment. This research is a quantitative research. The object of research to be examined are traders who are around the al-Musabbihin mosque in the Setia Budi Indah Park complex. The data collection technique used a questionnaire which was distributed to 45 traders around the Al-Musabbihin Mosque. This research was tested using the SPSS Version 22 test tool. The findings of this study are that capital and business volume have a significant effect on economic empowerment, coaching has no effect on the economic empowerment of the Al-Musabbihin mosque community. However, simultaneously capital, coaching and business volume have a significant effect on the economic empowerment of the Al-Musabbihin mosque community. Prospects for community economic empowerment can be increased by increasing capital, coaching and business volume. If the mosque functions as well as possible, it will reduce poverty in the surrounding environment and strengthen the local community's economy